(untitled) (Jurnal Geologi Pertambangan (JGP), 2018)
Aquilaria microcarpa from Thymeleaceae family is one of the high quality agarwood producing plants. Organic and inorganic fertilizers can increase the nutrients in the soil and increase the growth of agarwood plants. The purpose of this research is to know the effect of dolomite lime, chicken manure, and NPK on agarwood growth using single plant method with 5 treatments. The treatments are P0 : control (without treatment), P1 : chicken manure (2 kg), P2 : dolomite lime (100 gr), P3 : chicken manure (2 kg) and NPK (20 gr), and P4 : combination of chicken manure, NPK and dolomite lime. The research was carried out from October 2016 until May 2017. The results showed that the application of dolomite lime on agarwood plants gave significantly different results on plant vegetative growth, namely plant height, stem diameter, number of leaves, and number of branches, compared with other treatments. Keywords: Agarwood (Aquilaria microcarpa), fertilizer, revegetation, coal post-mining land.